Flower to Fruit Development in Coscinium fenestratum (Gaertn.) Colebr - C. R. Chitra; C. AnilKumar (Advanced Research in Biological Science Vol. 2, 2023)
This chapter highlights the flower to fruit development in Coscinium fenestratum (Gaertn.) Colebr., as an extensively used slow growing species often exploited for medicinal use. Despite the abundant seed production, there aren’t many seedlings in the wild, which led to a thorough investigation on its reproductive biology. As a dioecious liana, female plants can produce fruit even when there are no nearby male plants, and even the bagged, unopened flower buds eventually mature into seeds. A mysterious development is linked to the lack of pollinators, airborne pollen grains, and the production of a single seed from a tricarpillary gynoecium. In consequence of curiosity, flower and fruit development, studies on pollen viability, pollen germination, pollen ovule ratio and embryological studies etc were conducted. DNA isolation was done using the leaves of mother plant and seedlings raised from the same plant. High quality DNA was obtained from all the explants using the Modified CTAB method. The samples were diluted and ISSR analysis was carried out using 10 ISSR primers. Regardless of the lack of pollen on the stigma and pollen tube penetration into the stylar tube, embryo development was seen in 80% of the longitudinal microtome sections collected with fruit primordia that were aged from the first to third weeks. Genetic identity was also revealed by comparative molecular analyses of the mother plant and the corresponding F1 seedlings, which supported apomixis.